The Urgency of Implementation and Challenges of Merdeka Belajar Kampus Merdeka: An Analysis Study at State Higher Education in Kalimantan - Agus Salim; Evita Yuliatul Wahidah (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2023)
This study aims to describe and analyze the urgency of the Merdeka Belajar Kampus Merdeka program along with its implementation and challenges of higher education in Kalimantan, which has launched the Merdeka Learn-Independence Campus. It also identifies and evaluates the indicators for identifying Merdeka Belajar Kampus Merdeka, including student exchanges, internships/work practices, project assistance, economic activities, independent studies/projects, thematic KKN, and teaching assistance in education units. The research method used is descriptive analysis. Data was collected using literature and field studies. Interviews and observations were used in field studies. University-based data sources in Kalimantan include Tanjungpura University, Palangka Raya University, Lambung Mangkurat University, Mulawarman University, Borneo Tarakan University, and the Kalimantan Institute of Technology. The research findings show that the five tertiary institutions in Kalimantan have implemented the Merdeka Belajar Kampus Merdeka program by carrying out student exchange programs, apprenticeships/work practices, project assistance, economic activities, independent studies/projects, thematic KKN, and teaching assistance in higher education units. , while the implementation process is carried out highly sustainably by its singularity. The five tertiary institutions already have the capacity by the Merdeka Belajar Kampus Merdeka standards stipulated by laws and regulations.